1976
DOI: 10.1111/j.1749-6632.1976.tb41670.x
|View full text |Cite
|
Sign up to set email alerts
|

Subversive Activity of Syngeneic Tumor Cells as an Escape Mechanism From Immune Surveillance and the Role of Prostaglandins*

Abstract: Mice bearing a syngeneic tumor become increasingly immunodepressed during growth of the tumor, being unable to develop both cellular and humoral immunity to a histoincompatible tumor allograft and to reject the allograft. This failure to reject a strongly antigenic tumor allograft suggests that immunodepression associated with growth of a weakly antigenic syngeneic tumor provides the syngeneic tumor with an escape mechanism. This immunodepression is also manifest by the suppression of the response of spleen ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In other models, progressive tumors have been reported to produce soluble factors able to inhibit tumoricidal activities of T lymphocytes (Hellstrom and Hellstrom, 1970), macrophages (Cheung et al, 1979) and NK cells (Keong et al, 1983), or to prevent accumulation of tumoricidal macrophages at sites of inflammation (Fauve et al, 1974;Snyderman and Pike, 1976;Pasternack et al, 1978). Prostaglandins have been thought to be one of the potential immunosuppressive factors elaborated by progressive tumors (Plescia et al, 1976). However, prostaglandins do not play an important role in our model since TR cell growth in vivo is not significantly modified by indomethacin, a potent inhibitor of prostaglandin synthesis (Olsson et al, 1984).…”
Section: Lo6 Ts Cells With Splenic Cells From Tumor-bearing Ratsmentioning
confidence: 95%
See 1 more Smart Citation
“…In other models, progressive tumors have been reported to produce soluble factors able to inhibit tumoricidal activities of T lymphocytes (Hellstrom and Hellstrom, 1970), macrophages (Cheung et al, 1979) and NK cells (Keong et al, 1983), or to prevent accumulation of tumoricidal macrophages at sites of inflammation (Fauve et al, 1974;Snyderman and Pike, 1976;Pasternack et al, 1978). Prostaglandins have been thought to be one of the potential immunosuppressive factors elaborated by progressive tumors (Plescia et al, 1976). However, prostaglandins do not play an important role in our model since TR cell growth in vivo is not significantly modified by indomethacin, a potent inhibitor of prostaglandin synthesis (Olsson et al, 1984).…”
Section: Lo6 Ts Cells With Splenic Cells From Tumor-bearing Ratsmentioning
confidence: 95%
“…Prostaglandins have been thought to be one of the potential immunosuppressive factors elaborated by progressive tumors (Plescia et al, 1976). However, prostaglandins do not play an important role in our model since TR cell growth in vivo is not significantly modified by indomethacin, a potent inhibitor of prostaglandin synthesis (Olsson et al, 1984).…”
Section: Al 1976)mentioning
confidence: 96%
“…7.4.2.2 Effects of PGE 2 on T lymphocytes PGE 2 is immunosuppressive to various types of T cells through its inhibitory effects on proliferation, cytokine production, migration and effector activity (reviewed in [229,230]). Very early studies showed that immunization with PGE 2 significantly reduced tumor-induced immunosuppression (as measured by spleen cell proliferation assays) in mice [231,232], suggesting the role of PGE 2 in suppressing T cell proliferation. Further studies using experimental tumor models and anti-PGE 2 antibodies demonstrated the role of PGE 2 in suppressing polyclonal T cell activation and CTL generation following MLRs by splenic T cells [233].…”
Section: 42mentioning
confidence: 99%
“…Patients with Hodgkin's disease have been found to contain prostaglandin-producing suppressor cells which are believed to be responsible for the depressed cellular immunity in these patients (4). It has also been reported that prostaglandins inhibit the rejection of tumors (3,5); and prostaglandin of the E series, PGEl and PGE2, have been shown to inhibit the activation of cytotoxic T lymphocytes (CTL) (6,7). Prostaglandins have been shown to inhibit the proliferative response of lymphoid cells including interleukin-Z dependent cytolytic T-cell lines (8)(9)(10)(11)(12), reviewed in ( 1, 13)); and indomethacin and other inhibitors of prostaglandin synthesis have been shown to enhance the induction of cytotoxic responses against allogeneic cells (10).…”
Section: Introductionmentioning
confidence: 99%